(untitled) (Revista Electrónica REDINE, 2018)
To following we display a hand full of words that tries to be a reflection de application pertinent of the application of qualitative epistemologic – metodologic principles of order as they are in the fenomenologics and hermeneutics exposition in an investigation process. Basicly we refer about the experience lived by the authors in this process. The experience that me display derives from a study made with the students of the Degree of Integral Education of the National Experimental University Rafael María Baralt. Which had like propose to know the meaning that these assign to educative investigation within their development as professionals. As conclusion we considered that id becomes necessary the deepeming in the senses that the subject give to his practice daily since is there such they manage to construct the meaning which they articulate his own reality, which is unique. For it, the suitable epistemologic – metodologic tools are those that privilege the qualities and own characteristics of the subjects as fenomenologic and hermeneutic.